ANALISIS SENYAWA AKTIF DAUN WARU (Hibiscus tiliaceus) SEBAGAI ANTIBAKTERI TERHADAP Escherichia coli - Fatma, Nur Aida; Fitria, Fella Nur; Siswanto, Husna Malikatus; Sofa, Natilatus; R., Isma Salsabila; Sa'adah, Rizka Fadilla Naila; Wijaya, M. Achsan Hari; Fitriyah, Fitriyah; Saefi, Muhammad (Binar – Biology Natural Resources Journal, 2025)
Waru leaves (Hibiscus tiliaceus) are a plant that has bioactive potential with pharmacological benefits. This study aims to analyze the phytochemical content of waru leaves qualitatively, quantitatively, in silico, and their antibacterial activity against Escherichia coli. Qualitative analysis focuses on identifying bioactive compounds such as flavonoids, alkaloids, tannins, saponins, etc. The quantitative approach includes measuring total phenol and flavonoid levels using UV-Vis Spectrophotometry. In silico studies were carried out using the KNApSAcK Family website to identify compound classes, NCBI to obtain SMILES, SWISS ADME to predict pharmacokinetics, and WAY2DRUG PASS Prediction to determine the probability of biological activity. Antibacterial testing uses the diffusion method to determine the MIC and MBC values. The results showed that waru leaves contain various bioactive compounds with total phenolic levels of 30.416 mg GAE/g extract and total flavonoids of -0.476 mg QE/g extract. In silico testing shows that Hibiscus tiliaceus has a unique bioactive compound, namely Hibiscoquinone A, which has potential as a drug candidate with antibacterial activity, lipid peroxidase inhibitor, and ubiquinol-cytochrome-c reductase inhibitor. Antibacterial testing of hibiscus leaf extract against E. coli using the diffusion method obtained MIC values ​​at concentrations of 15% and 30%. However, at these concentrations it did not show MBC values. This research provides scientific evidence regarding the potential of waru leaves as a herbal medicine in treating infectious diseases caused by bacteria.